A Straightforward Method for Synthesizing Bioactive Resorcinolic Lipid Analogues - dos Santos, Denilson Silva; Meza, Alisson; Gomes, Roberto da Silva; de Lima, Dênis Pires; Beatriz, Adilson (Orbital: The Electronic Journal of Chemistry, 2020)
Resorcinolic lipids, a class of bioactive amphiphilic molecules found widely in nature, hold potential for a variety of biological and industrial applications. This report describes the synthesis of three bioactive structural analogues of resorcinolic lipids, obtained by subjecting ethyl (E)-2-undecenoate and ethyl acetoacetate to a Michael reaction in the presence of sodium ethoxide to generate a Michael adduct, followed by cyclization in the reaction medium. Ethyl 2-octyl-4,6-dioxocyclohexanecarboxylate (7) was thus produced with a 60% yield. To perform an aromatization step, 7 was subsequently treated with I2 in methanol under reflux, producing a combined 80% yield of 2,4-dimethoxy-6-octyl-ethyl benzoate (1) and 2-hydroxy-4-methoxy-6-octyl-ethyl benzoate (2) at a 7:3 ratio, respectively. 2-Hydroxy-4-methoxy-6-octyl-benzoic acid was obtained with a 60% yield by treating 1 with BBr3/CHCl3. The structures of the synthesized compounds and intermediates were elucidated by 1H and 13C NMR spectroscopy, employing two-dimensional techniques (HSQC and HMBC).DOI: http://dx.doi.org/10.17807/orbital.v12i2.237